The Lift Enhancement Effect of a New Fluidic Oscillator on High-Lift Wings - Tong Zhao; Yalei Bai (Aerospace, 2025)
Fluidic oscillators have emerged as a prominent topic of research in the field of flow control, owing to their broad sweep range and enhanced control efficiency. However, the underlying mechanisms governing the operation of fluidic oscillators remain poorly understood, and the effect of oscillation frequency on flow control performance has yet to be conclusively determined. In this study, a novel fluidic oscillator is proposed that achieves frequency decoupling by replacing the conventional feedback channel with synthetic jets, thereby enabling modulation of oscillation frequency at a constant momentum coefficient. When applied to a high-lift airfoil, results show that at a momentum coefficient of 14.1%, the lift coefficient increase achieved under F+ = 1 control outperforms that under F+ = 10 by more than 0.3. This finding suggests the presence of an optimal frequency for fluidic oscillators, which maximizes their flow control effectiveness. Notably, this optimal frequency is unaffected by variations in the momentum coefficient. A deeper analysis of the fluidic oscillator’s working principle reveals that periodic oscillations dominate the turbulent kinetic energy and Reynolds shear stress, driving enhanced chordwise momentum exchange. This increased energy transfer strengthens the boundary layer’s resistance to separation, effectively mitigating flow detachment and improving lift enhancement. Finally, the periodic flow field on the surface of the high-lift airfoil under fluidic oscillator control was examined. It was observed that, at low frequencies, the fluidic oscillator effectively controls the shedding of separation vortices, ensuring that the frequency of vortex shedding aligns with the oscillation frequency of the fluidic oscillator. This alignment likely contributes to the superior lift enhancement observed under low-frequency conditions.